Feasibility and acceptability of novel functional electronic stimulated rehabilitation application for treatment in patients with cerebrovascular disorders: the FRAT study protocol - Tomoo Mano; Kiyoshi Asada; Shota Suzuki; Shu Kasama; Kaoru Kinugawa; Kazuma Sugie; Masato Kasahara; Akira Kido (Pilot and Feasibility Studies, 2022)
Abstract Background The prognosis of patients with cerebrovascular disorders is poor owing to their high residual rate of hemiplegia. Delayed withdrawal from synkinesis is a major cause of prolonged hemiplegia; however, effective rehabilitation has not been established. This single-arm, open-label study aims to evaluate the influence of a low-frequency treatment device on canceling synkinesis in patients with incomplete paralysis and cerebrovascular disorders. Methods Eligible participants will include patients aged 20 years or older with incomplete paralysis, defined as upper limb Brunnstrom stage (BRS) of 2–4, who are within 1 month of onset of a cerebrovascular disorder. Qualified patients will be assigned to the novel rehabilitation treatment with IVES+ for 4 weeks. The primary endpoint of the study is the change from baseline in the upper-limb Fugl-Meyer Assessment (FMA) 2 weeks after the start of treatment. The secondary endpoints are changes in the amount of Functional Independence Measure, changes in the amount of upper-limb BRS, and changes in the amount of Barthel Index (BI) compared to the pre-intervention value at weeks 2 and 4; changes in the upper-limb FMA scores at 1, 3, and 4 weeks; changes in grip strength compared to the pre-intervention values at 1, 2, 3, and 4 weeks; and changes in upper-limb strength (manual muscle test) compared to the pre-intervention values at 1, 2, 3, and 4 weeks. Discussion This study will explore the usefulness of IVES+ for recovery from motor paralysis in patients with cerebrovascular disorders. Trial registration Japanese Clinical Registry, jRCTs052180226. Date of registration: February 1, 2022